2014
DOI: 10.1039/c3cp54917h
|View full text |Cite
|
Sign up to set email alerts
|

Solid state chemistry of nitrogen oxides – Part I: surface consumption of NO

Abstract: The role of nitrogen and oxygen chemistry in the interstellar medium is still rather poorly understood.Nitric oxide, NO, has been proposed as an important precursor in the formation of larger N-and O-bearing species, such as hydroxylamine, NH 2 OH, and nitrogen oxides, Temperature Programmed Desorption (TPD) using mass spectrometry. We find that NO 2 is efficiently formed in NO + O/O 2 /O 3 /N solid surface reactions. These are essentially barrier free and offer a pathway for the formation of NO 2 in space. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 55 publications
3
43
0
Order By: Relevance
“…FIGURE 10 -The complete nitrogen chemistry network, summarizing the findings from [126][127][128][129][130][131][132][133][134].…”
Section: Surface Chemistry Of Nitrogen Bearing Moleculesmentioning
confidence: 99%
“…FIGURE 10 -The complete nitrogen chemistry network, summarizing the findings from [126][127][128][129][130][131][132][133][134].…”
Section: Surface Chemistry Of Nitrogen Bearing Moleculesmentioning
confidence: 99%
“…2 for more details on TPD-QMS data). Along with traces of cis-(NO)2, also weak signals due to NO monomers can be resolved after UV-processing of the ice through their characteristic absorption at 1875 cm -1 (Fateley et al 1959, Fedoseev et al 2012, Minissale et al 2014. Wavelength, m Wavelength, m The total H-atom fluence is 6x10 16 atoms cm -2 .…”
Section: Simultaneous Hydrogenation and Uv-processing Of Pure Nomentioning
confidence: 99%
“…This is particularly important under the extremely cold conditions of the interstellar medium (ISM), where gas-phase and surface reactions are strongly affected by even small endothermicity or the presence of an activation barrier. Recently, frozen NO molecules have been linked to the formation of other species, like NH2OH, NO2, N2O, and HNO2 (Joshi et al 2012, Congiu et al 2012a, Congiu et al 2012b, Fedoseev et al 2012, Minissale et al 2014, Ioppolo et al 2014a. In space, NO molecules are primarly formed in the gas-phase through the reaction: N (g) + OH (g) → NO (g) + H (g) (1), (see Herbst & Klemperer 1973, McGonagle et al 1990, Gerin et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Laboratory studies of non-energetic surface processing showed that, for instance, ammonia (NH 3 ), hydroxylamine (NH 2 OH), nitrogen dioxide (NO 2 ), dinitrogen trioxide (N 2 O 3 ), nitrous acid (HNO 2 ), and nitric acid (HNO 3 ) are efficiently formed at low temperatures through hydrogenation of N-atoms, NO + H, NO + O 2 , NO + NO 2 , NO + OH, and NO 2 + OH reactions, respectively. [9][10][11][12][13][14][15][16] In the accompanying paper, hereafter referred to as Part I, 17 we investigate the oxygenation of solid NO (NO + O/O 2 /O 3 ) at a Division of Geological and Planetary Sciences, California Institute of Technology,…”
Section: Introductionmentioning
confidence: 99%